Pelatihan Technopreneurship bagi Kelompok Pengrajin Rotan di Kelurahan Balearjosari Kota Malang - Sudarmiatin Sudarmiatin; Rayie Tariaranie Wiguna; Adelia Sabrina Pramega (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this service activity is to provide technopreneurship training to rattan craftsmen in order to increase sales turnover. The method used consists of 3 stages, namely; (1) FGD with rattan craftsmen; (2) Provide training to create and operate business Instagram with link_tree; (3) Provide consultation and assistance so that online businesses can run independently. The results of the activity showed that there was an increase in knowledge and technopreneurship skills in the rattan craftsman group by 50%, after having an online business account the craftsman's attitude became more optimistic in facing the future, the formation of business Instagram marketing media with link_tree to increase sales of rattan handicrafts.